The Correlation Of Knowledge On Cervical Cancer With Early Detection Of Cervical Cancer Among Women Of Childbearing Age In Tanah Datar Pekan Heran Indragiri Hulu Regency - Nina Selvia Artha (JURNAL PROTEKSI KESEHATAN, 2020)
AbstractCervical cancer is one of malignant neoplasms and number one cancer killer ofwomen in Indonesia. The aim of this research is to Know the Correlation KnowledgeWomen of Childbearing Age (WCA) With Early Detection of Cervical Cancer inTanah Datar Village Working Area of Puskesmas Pekan Heran Indragiri HuluRegency. The research design used descriptive correlation with approach crosssectional. The sampling technique used is purposive sampling and random samplingwith the number of 227 respondents. The processing data using univariate andbivariate analysis with Chisquare test. The results obtained were the of WCA whohad enough knowledge about cervical cancer as many as 99 respondents(43,6%) and early detection of cervical cancer with method IVA test by WUSmajority did not early detection as much as 174 respondents (76,7%). Chi-Squarestatistical test results obtained that the correlation knowledge with early detectionof cervical cancer is p value 0,00 < 0.05. Conclusion: There is a Correlationbetween Knowledge Women of Childbearing Age (WCA) With Early Detectionof Cervical Cancer in Tanah Datar Village Working Area of Puskesmas PekanHeran Indragiri Hulu Regency.